PENGARUH STRATEGI INKUIRI SOSIAL TERHADAP PEMAHAMAN IPS DAN SELF-REGULATED LEARNING SISWA SEKOLAH DASAR PADA MATERI KEGIATAN EKONOMI DI INDONESIA (Penelitian Kuasi Eksperimen terhadap Siswa Kelas VA dan VB SDN Sukalilah Kecamatan Pamulihan Kabupaten Sumedang) - Purwasih, Pupun; Gusrayani, Diah; Hanifah, Nurdinah (Jurnal Pena Ilmiah, 2017)
The researched was purposed to find out whether there was any significant increasing who have been taught of social science and self-regulated learning from student by using social inquiries strategy and conventional strategy, to knowing correlation between understanding of the social science and self-regulated learning of students. This type of the research is quasi experimental with using non equivalent control group design. The population is all of student of 5th grade of elementary school in Pamulihan District. The results of data analysis showed that no significant a difference between experimental class or control, value of P-value (2-tailed) for amount 0,096 ≥ 0,05 impact on H0 for received and H1 for rejected. And there is no difference between learning using social inquiries strategy and conventional strategy to improving self regulated learning of the students to show 0,079 ≥ 0,05 impact on H0 for received and H1 for rejected. There is no related to understanding between a social science with self regulated learning students is value of P-value (2-tailed) for amount 0,580 ≥ 0,05, so that the value H0 for received and H1 for rejected.